2000
DOI: 10.1523/jneurosci.20-19-07334.2000
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Regulated Exocytotic Carriers in Neuroendocrine Cells

Abstract: Ca(2+)-triggered exocytosis is a hallmark of neurosecretory granules, but the cellular pathway leading to the assembly of these regulated exocytotic carriers is poorly understood. Here we used the pituitary AtT-20 cell line to study the biogenesis of regulated exocytotic carriers involved in peptide hormone secretion. We show that immature secretory granules (ISGs) freshly budded from the trans-Golgi network (TGN) exhibit characteristics of unregulated exocytotic carriers. During a subsequent maturation period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(119 citation statements)
references
References 29 publications
8
110
0
Order By: Relevance
“…In brief, two oligonucleotides (sense, 5Ј-TCATCACCGTCA-GCCTTAGTTCAAGAGACTAAGGCTGACGGTGATGATTTTTT-3Ј and ; yellow in C, F, and L, respectively), especially at the tips of the cellular processes, consistent with the results of our previous subcellular fractionation study (40). Because the Syt IV protein in undifferentiated PC12 cells is mainly localized in the Golgi and immature secretory vesicles (49,50,67), no colocalization between Syt VII-GFP and Syt IV was observed even in the tips of the cellular processes (I, inset, arrow) or in the perinuclear region. Confocal images were taken to highlight the localization of Syt VII-GFP in the tips of the cellular processes (i.e.…”
Section: Construction Of Psilencer-syt VII Vectors For Syt Vii Silencsupporting
confidence: 86%
“…In brief, two oligonucleotides (sense, 5Ј-TCATCACCGTCA-GCCTTAGTTCAAGAGACTAAGGCTGACGGTGATGATTTTTT-3Ј and ; yellow in C, F, and L, respectively), especially at the tips of the cellular processes, consistent with the results of our previous subcellular fractionation study (40). Because the Syt IV protein in undifferentiated PC12 cells is mainly localized in the Golgi and immature secretory vesicles (49,50,67), no colocalization between Syt VII-GFP and Syt IV was observed even in the tips of the cellular processes (I, inset, arrow) or in the perinuclear region. Confocal images were taken to highlight the localization of Syt VII-GFP in the tips of the cellular processes (i.e.…”
Section: Construction Of Psilencer-syt VII Vectors For Syt Vii Silencsupporting
confidence: 86%
“…As shown in Fig. 2A, [ 35 S]Syt I was retained by an immobilized N-TRPV1-His fusion protein. Similarly, Syt I was preferentially bound to the core ankyrin repeats.…”
Section: Syt IX and Snapin Interact With The N Terminus Of Trpv1-mentioning
confidence: 84%
“…5, C, D, and F). Because it has been shown that overexpression of SNARE proteins may abrogate SNARE-dependent exocytosis (35), this finding suggests that TRPV1 potentiation by PKC may occur partly by the rapid recruitment of vesicle-associated channel molecules to the cell surface by exocytosis.…”
Section: Fig 6 Potentiation Of Trpv1 Activity By Mglur5 Activationmentioning
confidence: 98%
See 1 more Smart Citation
“…The formation of secretory granules is thought to be a signal mediated process, with roles proposed for small GTP-binding proteins, heterotrimeric G proteins, protein phosphorylation and dephosphorylation, and phospholipase D (Austin and Shields, 1997;Urbe et al, 1997;Ktistakis, 1998;Tooze, 1998). As granules mature, they acquire responsiveness to secretagogue (Mains and Eipper, 1981;Arvan et al, 1991), a process that involves removal of specific proteins (Kuliawat et al, 1997;Eaton et al, 2000).…”
Section: Signaling Through P-cip2 Allows Pam To Affect Trafficking Inmentioning
confidence: 99%